Comparative transcriptome study of switchgrass (Panicum virgatum L.) homologous autopolyploid and its parental amphidiploid responding to consistent drought stress - Peilin Chen; Jing Chen; Min Sun; Haidong Yan; Guangyan Feng; Bingchao Wu; Xinquan Zhang; Xiaoshan Wang; Linkai Huang (Biotechnology for Biofuels, 2020)
Abstract Background Newly formed polyploids may experience short-term adaptative changes in their genome that may enhance the resistance of plants to stress. Considering the increasingly serious effects of drought on biofuel plants, whole genome duplication (WGD) may be an efficient way to proceed with drought resistant breeding. However, the molecular mechanism of drought response before/after WGD remains largely unclear. Result We found that autoploid switchgrass (Panicum virgatum L.) 8X Alamo had higher drought tolerance than its parent amphidiploid 4X Alamo using physiological tests. RNA and microRNA sequencing at different time points during drought were then conducted on 8X Alamo and 4X Alamo switchgrass. The specific differentially expressed transcripts (DETs) that related to drought stress (DS) in 8X Alamo were enriched in ribonucleoside and ribonucleotide binding, while the drought-related DETs in 4X Alamo were enriched in structural molecule activity. Ploidy-related DETs were primarily associated with signal transduction mechanisms. Weighted gene co-expression network analysis (WGCNA) detected three significant DS-related modules, and their DETs were primarily enriched in biosynthesis process and photosynthesis. A total of 26 differentially expressed microRNAs (DEmiRs) were detected, and among them, sbi-microRNA 399b was only expressed in 8X Alamo. The targets of microRNAs that were responded to polyploidization and drought stress all contained cytochrome P450 and superoxide dismutase genes. Conclusions This study explored the drought response of 8X and 4X Alamo switchgrass on both physiological and transcriptional levels, and provided experimental and sequencing data basis for a short-term adaptability study and drought-resistant biofuel plant breeding.